The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/1735-9066.170005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of progressive muscle relaxation on pregnant women's general health

Abstract: Background:Pregnancy may be accompanied by serious physiological and psychological changes as it is a stressful period in a woman's life. So, this study was conducted to determine the effect of progressive muscle relaxation on pregnant women's general health.Materials and Methods:In this clinical trial, 60 primigravida women admitted to the prenatal clinic of selected hospitals in Iran constituted the study population. Using purposive sampling method, the level of general health of the women was measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Zargarzadeh et al demonstrated that relaxation exercises had a positive effect on reducing students' test anxiety. 26 Also, Ahmadnejad and colleagues investigated the effects of relaxation techniques on decreasing anxiety among students in a clinical experience and realized it to be helpful. 27 Heidari et al revealed that teaching muscular relaxation techniques and gradually releasing tension, combined with biofeedback, significantly reduces students’ anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Zargarzadeh et al demonstrated that relaxation exercises had a positive effect on reducing students' test anxiety. 26 Also, Ahmadnejad and colleagues investigated the effects of relaxation techniques on decreasing anxiety among students in a clinical experience and realized it to be helpful. 27 Heidari et al revealed that teaching muscular relaxation techniques and gradually releasing tension, combined with biofeedback, significantly reduces students’ anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The study started on May 3, 2013 and ended on August 7, 2013. The sample size was obtained by using Altman's nomogram and considering the previous studies as samples,[ 10 ] with power = 90%, α = 10% and β = 5%, following screening and written consent, the participants were divided into equal numbers of three groups, using a ball inside a bag. They were requested to participate actively in the random assignment.…”
Section: Methodsmentioning
confidence: 99%
“…So, we selected participants for each group by randomization. The inclusion criteria were nulliparous and maximum of 12 weeks of gestational age ( first trimester) according to the previous study,[ 10 ] minimum literacy required for reading and understanding the stages of PA, single pregnancy, low-risk pregnancy, no use of antidepressants, and no addiction to cigarettes, opioids, or alcohol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations